Galloping through Culture: Horse Racing and Global History: Review of The Running Centaur: Horse-Racing in Global-Historical Perspective, ed. Sinclair W. Bell, Christian Jaser and Christian Mann - Willekes, Carolyn (Humanimalia, 2023)
Sinclair W. Bell, Christian Jaser and Christian Mann, eds., The Running Centaur: Horse-Racing in Global-Historical Perspective. London: Routledge, 2022. 216 pp. $160 (hb).